Monstruo, vas a comerme? - Menaya, Purificacion; Steinmeyer, Petra (Barcelona : Bambu Editorial, 2008)
A boy finds a monster under his bed and thinks the monster wants to eat him. In reality, the monster doesn't like eating children. Instead, he likes chewing on bedtime stories.
Keywords: Monsters -- Juvenile fiction; Bedtime -- Juvenile fiction; Monstruos -- Novela juvenil; Hora de acostarse -- Novela juvenil